2023
DOI: 10.1002/cctc.202201272
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Protection of a Water‐Soluble Olefin Metathesis Catalyst for Potential Use under Biological Conditions

Abstract: Olefin metathesis catalysts like AquaMet are vulnerable to different decomposition pathways under biologically relevant conditions. Currently, stabilizing strategies are focused on approaches with limited relevance for application under biologically relevant conditions. Initial attempts to stabilise AquaMet by encapsulation within a supramolecular metallocage showed that the nitrate counterions of the cage improve the activity of the catalyst. We show that the chloride ligands of AquaMet can be replaced with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…The best results were achieved with 2.5 mol % catalyst and 100 mM substrate in the presence of 140 mM NaCl, a salt being naturally present in the cellular environment. With the optimized conditions at hand, the reaction was then performed in a home‐built automated ‘bubble counter’ device [34,35] (See SI for more details; Figure S1) to monitor the volumetric evolution of ethene gas over the course of the reaction (Figure S4) [36] . After reaction completion, the yield of the 2‐butene‐1,4‐diol product was also determined from the same reaction mixture by 1 H NMR spectroscopy using an external standard (See SI for more details; Figure S5, Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best results were achieved with 2.5 mol % catalyst and 100 mM substrate in the presence of 140 mM NaCl, a salt being naturally present in the cellular environment. With the optimized conditions at hand, the reaction was then performed in a home‐built automated ‘bubble counter’ device [34,35] (See SI for more details; Figure S1) to monitor the volumetric evolution of ethene gas over the course of the reaction (Figure S4) [36] . After reaction completion, the yield of the 2‐butene‐1,4‐diol product was also determined from the same reaction mixture by 1 H NMR spectroscopy using an external standard (See SI for more details; Figure S5, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…With the optimized conditions at hand, the reaction was then performed in a home-built automated 'bubble counter' device [34,35] (See SI for more details; Figure S1) to monitor the volumetric evolution of ethene gas over the course of the reaction (Figure S4). [36] After reaction completion, the yield of the 2-butene-1,4-diol product was also determined from the same reaction mixture by 1 H NMR spectroscopy using an external standard (See SI for more details; Figure S5, Table S2). These measurements were done to 1) confirm that one equivalent of ethene is formed alongside one equivalent of product and 2) establish that ethene evolution is a reliable measure for the yield and can therefore be used to obtain kinetic profiles of the model reaction under biomimetic conditions.…”
Section: Protocol Validationmentioning
confidence: 99%
“…Reek et al have recently demonstrated this kinetic protection for a ring-closing metathesis reaction under biological conditions in the lab, where a catalyst with faster reaction rates is able to generate higher amounts of the desired product in the presence of poisonous biomolecules compared to a similar catalyst with much slower reaction rates. [66] Although this strategy works well for this metathesis reaction, in-depth mechanistic insights may be required in order to apply this concept to other reactions.…”
Section: Kinetic Protection Of the Catalystmentioning
confidence: 99%
“…With the optimized conditions at hand, the reaction was then performed in a home-built automated "bubble counter" device [27], [28] (See SI for more details; Figure S1) to monitor the volumetric evolution of ethene gas over the course of the reaction (Figure S4). [29] After reaction completion, the yield was also determined by 1 H NMR spectroscopy to 1) confirm that one equivalent of ethene is formed alongside one equivalent of product, and 2) establish that ethene evolution is a reliable measure for the yield and can therefore be used to obtain kinetic profiles of the model reaction under biomimetic conditions (Figure S5, Table S2). The reproducibility of this protocol was confirmed by a duplicate experiment that afforded an identical kinetic profile and yield compared to the first reaction.…”
mentioning
confidence: 99%